Photocatalyst Nanostructured Tio₂ Powder by Using Hydrothermal Method: a Review - Shamsudin, S.; K. Ahmad, M.; Nafarizal, N.; F. Soon, C.; A. Rahim, R.; H. Mamat, M.; B. Suriani, A.; Shimomura, M.; Murakami, K. (International Journal of Engineering and Technology, 2019)
Over the past decades, Titanium dioxide (TiO₂) have been studied extensively that give positive impact to its synthesis and fabrication method that resulting discovery of a simple low-temperature hydrothermal method that makes the nanostructure of TiO₂ easily modified according to the desired application. This paper presents a review of photocatalyst nanostructured TiO₂ by using hydrothermal method as its fabrication method. The TiO₂ powder widely used as a photocatalytic application that mainly for self-cleaning and wastewater treatment.  Rutile phase is stable in the high-temperature region compared to anatase and brookite that metastable in high temperature and photo-catalytic activity, PCA could be enhanced by increasing the number of oxygen. By manipulating the preparation method and thermal treatment, a superior photocatalyst with high surface area and crystallinity which correlated to photocatalytic performance was able to produce. In addition to this, photocatalytic activity of TiO₂ is substantially dependent on the crystal size, specific surface area, crystal defects, charge separation capacity and the interface between the photocatalyst and the molecules.